Potamogeton schweinfurthii in the Iberian Peninsula - Pere Aymerich; Zdenek Kaplan; Moisès Guardiola; Albert Petit; Udo Schwarzer (Anales del Jardín Botánico de Madrid, 2012)
We provide the first records for the Iberian Peninsula of Potamogeton schweinfurthii A. Benn., a species distributed mainly in Africa that was not discovered in Europe until 2005, where it is assumed to be indigenous but it has generally been confused with P. lucens. The Iberian specimens, which for the most part are from recent collections, have been identified based on morphological characteristics and molecular studies. We have detected 8 localities, 4 in the northeastern area of the Peninsula (Catalonia and Navarra) and 4 from the West (south and north of Portugal and western Andalusia). Our studies show that it is a very rare species on a regional level. Although it is a mainly tropical and subtropical species, we have found that P. schweinfurthii (both natural populations and those cultivated) has a high tolerance to climates with severe winters and frequent frosts. The large proportion of populations found in anthropogenic habitats, and the fact that most European records are from the past half-century, suggest that P. schweinfurthii may have experienced a recent expansion favoured by the construction of large number of artificial water bodies in the Mediterranean region. This raises the possibility that P. schweinfurthii in Europe is a species that forms temporary populations and has a naturally unstable area.